# Find $b_{32}$ if $\prod_{n=1}^{32}(1-z^n)^{b_n}\equiv 1-2z \pmod{z^{33}}$ and $b_n\in\mathbb{Z}^{+}$

A polynomial product of the form $$(1 - z)^{b_1} (1 - z^2)^{b_2} (1 - z^3)^{b_3} (1 - z^4)^{b_4} (1 - z^5)^{b_5} \dotsm (1 - z^{32})^{b_{32}},$$where the $$b_k$$ are positive integers, has the surprising property that if we multiply it out and discard all terms involving $$z$$ to a power larger than 32, what is left is just $$1 - 2z.$$ Determine $$b_{32}.$$

I tried letting this polynomial equal to $$z^{32}q(z) + 1-2z$$, but I don't see how this can help.

I also tried to solve simpler versions of the problem, such as finding $$b_2$$ if the product was $$(1-z)^{b_1}(1-z^2)^{b_2}$$. I found that the product $$(1-z)^2(1-z^2)^1$$ works. I then tried to solve the problem when the product was $$(1-z)^{b_1}(1-z^2)^{b_2}(1-z^3)^{b_3}$$. However, this got quite confusing, and I'm not sure what to do other than randomly test numbers. Now I'm not sure what I should do next.

• $b_n$ can be defined recursively by $\displaystyle\;b_n = \begin{cases}2, & n = 1\\ [z^n] \prod\limits_{k=1}^{n-1}(1-z^k)^{b_k}, & 1 < n \le 32\end{cases}\;$ where $[z^n]$ stands for coefficients of $z^k$ of polynomial on its left. By quasi brute force, I get $$(b_1,b_2,\ldots,b_{32}) = (2,1,2,3,6,9,18,30,56,99,\ldots, 69273666,134215680)$$ and an OEIS search returns A001037. May 4, 2022 at 18:24
It turns out that, for any $$n\in\mathbb{Z}^+$$ and $$a\in\mathbb{Z}$$, the unique solution $$(b_1,\ldots,b_n)\in\mathbb{Z}^n$$ to $$\prod_{k=1}^{n}(1-z^k)^{b_k}\equiv 1-az\pmod{z^{n+1}}\tag{1}\label{eqtn}$$ is given by $$b_k=\frac1k\sum_{d\,\mid\,k}\mu(d)a^{k/d}\tag{2}\label{sltn}$$ using the Möbius function $$\mu$$; note the independence on $$n$$. Thus the answer is $$\color{blue}{2^{11}(2^{16}-1)}$$.
Let $$\ell(z)=-\log(1-z)=\sum_{n=1}^\infty z^n/n$$; then \eqref{eqtn} implies $$\sum_{k=1}^n b_k\ell(z^k)\equiv\ell(az)\pmod{z^{n+1}},$$ that is $$\sum_{m=1}^n\frac{a^m}{m}z^m=\sum_{k=1}^n b_k\sum_{d=1}^{\lfloor n/k\rfloor}\frac{z^{kd}}{d}=\sum_{m=1}^n z^m\sum_{d\,\mid\,m}\frac{b_{m/d}}{d},$$ i.e. $$a^m=\sum_{d\,\mid\,m}(m/d)b_{m/d}=\sum_{d\,\mid\,m}db_d$$, and \eqref{sltn} follows by Möbius inversion.